Ceramic Heads Decrease Metal Release Caused by Head‐taper Fretting and Corrosion. Issue 4 (April 2016) - Kocagoz, Sevi B.; Underwood, Richard J.; MacDonald, Daniel W.; Gilbert, Jeremy L.; Kurtz, Steven M.
Abstract: Background: Metal release resulting from taper fretting and corrosion is a clinical concern, because wear and corrosion products may stimulate adverse local tissue reactions. Unimodular hip arthroplasties have a conical taper between the femoral head (head bore taper) and the femoral stem (stem cone taper). The use of ceramic heads has been suggested as a way of reducing the generation of wear and corrosion products from the head bore/stem cone taper junction. A previous semiquantitative study found that ceramic heads had less visual evidence of fretting‐corrosion damage compared with CoCr heads; but, to our knowledge, no studies have quantified the volumetric material loss from the head bore and stem cone tapers of a matched cohort of ceramic and metal heads. Questions/purposes: We asked: (1) Do ceramic heads result in less volume of material loss at the head‐stem junction compared with CoCr heads; (2) do stem cone tapers have less volumetric material loss compared with CoCr head bore tapers; (3) do visual fretting‐corrosion scores correlate with volumetric material loss; and (4) are device, patient, or intraoperative factors associated with volumetric material loss? Methods: A quantitative method was developed to estimate volumetric material loss from the head and stem taper in previously matched cohorts of 50 ceramic and 50 CoCr head‐stem pairs retrieved during revision surgery for causes not related to adverse reactions to metal particles. The cohorts were matched according to (1) implantation time, (2) stem flexural rigidity, and (3) lateral offset. Fretting corrosion was assessed visually using a previously published four‐point, semiquantitative scoring system. The volumetric loss was measured using a precision roundness machine. Using 24 equally spaced axial traces, the volumetric loss was estimated using a linear least squares fit to interpolate the as‐manufactured surfaces. The results of this analysis were considered in the context of device (taper angle clearance, head size, head offset, lateral offset, stem material, and stem surface finish) and patient factors that were obtained from the patients' operative records (implantation time, age at insertion, activity level, and BMI). Results: The cumulative volumetric material losses estimated for the ceramic cohort had a median of 0.0 mm 3 per year (range, 0.0‐0.4 mm 3 ). The cumulative volumetric material losses estimated for the CoCr cohort had a median of 0.1 mm 3 per year (range, 0.0‐8.8 mm 3 ). An order of magnitude reduction in volumetric material loss was found when a ceramic head was used instead of a CoCr head (p < 0.0001). In the CoCr cohort, the femoral head bore tapers had a median material loss of 0.02 mm 3 (range, 0.0‐8.7 mm 3 ) and the stem cone tapers had a median material loss of 0.0 mm 3 (range, 0.0‐0.32 mm 3 /year). There was greater material loss from femoral head bore tapers compared with stem cone tapers in the CoCr cohort (p < 0.001). There was a positive correlation between visual scoring and volumetric material loss (Spearman's ρ = 0.67, p < 0.01). Although visual scoring was effective for preliminary screening to separate tapers with no or mild damage from tapers with moderate to severe damage, it was not capable of discriminating in the large range of material loss observed at the taper surfaces with moderate to severe fretting‐corrosion damage, indicated with a score of 3 or 4. We observed no correlations between volumetric material loss and device and patient factors. Conclusions: The majority of estimated material loss from the head bore‐stem cone junctions resulting from taper fretting and corrosion was from the CoCr head bore tapers as opposed to the stem cone tapers. Additionally, the total material loss from the ceramic cohort showed a reduction in the amount of metal released by an order of magnitude compared with the CoCr cohort. Clinical Relevance: We found that ceramic femoral heads may be an effective means by which to reduce metal release caused by taper fretting and corrosion at the head bore‐stem cone modular interface in THAs.